Convenio de pago como modo de extinguir las obligaciones del sector público - Padilla Jara, Alejandro David (2024)
This research addresses the issue of payment agreements as a mechanism to extinguish obligations in the Ecuadorian public sector, exploring its legal basis and practical effectiveness. This study delves into current regulations and their application, highlighting how these agreements facilitate the management of state debts in a way that balances liquidity requirementsand continuity in the provision of public services. Through a qualitative methodological approachthat includes analysis of doctrine, jurisprudence, and interviews with professionals in the sector, the capacity of these agreements to resolve financial commitments ethically and in accordance with the law is examined. The research reveals a notable lack of specific legislation thatexhaustively regulates these agreements, a situation that poses significant challenges for their effective implementation. The need to strengthen the legal framework is identified to ensure that payment agreements not only satisfy basic legal requirements but are also managed under principles of transparency and justice, avoiding corrupt or arbitrary practices. It is argued that adequate and detailed regulation could considerably improve legal certainty and efficiency in public administration. Furthermore, the implications of these agreements on fiscal sustainability and public trust are discussed, suggesting that appropriate management can strengthen governanceand promote transparency in public management. The research concludes that payment agreements represent a valuable and necessary tool for state debt management, but it is crucial toaddress legal gaps and practical challenges to optimize their effectiveness and ensure they contribute to the common good.